Implementasi Kegiatan Tangkap Bola untuk Meningkatkan Motorik Kasar Anak di RA Miftahul Hidayah - Kurniawan, Nurhafit (Education Journal : Journal Educational Research and Development, 2024)
This study aims to improve the gross motor skills of children aged 4-5 years at RA Miftahul Hidayah through ball games and catching activities. Gross motor skills are a crucial aspect of child development and include basic physical abilities such as hand-eye coordination, balance, and physical strength. This research employs Classroom Action Research (CAR) using the Kemmis and Taggart cycle model. The findings show that after participating in ball-catching activities, the children's gross motor skills significantly improved, with a success rate of 75% in the second cycle. Although these results indicate that ball-catching is an effective strategy for developing children's gross motor skills, challenges remain, including differences in the children's initial abilities and the need for adjustments in teaching methods.